Endocranial Morphology of the Primitive Nodosaurid Dinosaur Pawpawsaurus campbelli from the Early Cretaceous of North America. - Ariana Paulina-Carabajal; Yuong-Nam Lee; Louis L Jacobs (PLoS ONE, 2016)
Background Ankylosaurs are one of the least explored clades of dinosaurs regarding endocranial anatomy, with few available descriptions of braincase anatomy and even less information on brain and inner ear morphologies. The main goal of this study is to provide a detailed description of the braincase and internal structures of the Early Cretaceous nodosaurid Pawpawsaurus campbelli, based on recently made CT scans. Methodology/principal findings The skull of Pawpawsaurus was CT scanned at University of Texas at Austin (UTCT). Three-dimensional models were constructed using Mimics 18.0 (Materialise). The digital data and further processed 3D models revealed inaccessible anatomic structures, allowing a detailed description of the lateral wall of the braincase (obscured by other bones in the articulated skull), and endocranial structures such as the cranial endocast, the most complete inner ear morphology for a nodosaurid, and the interpretation of the airflow system within the nasal cavities. Conslusions/significance The new information on the endocranial morphology of Pawpawsaurus adds anatomical data to the poorly understand ankylosaur paleoneurology. The new set of data has potential use not only in taxonomy and phylogeny, but also in paleobiological interpretations based on the relative development of sense organs, such as olfaction, hearing and balance.